Hybrid MAC Scheme for Vehicular Communications. (17th November 2013) - Cho, Woong
Abstract : Vehicular communications have been creating new applications in intelligent transportation systems (ITS) areas by converging information and communication technology (ICT) with automobile and road industries. In this paper, we introduce hybrid MAC scheme for vehicular communications which enhances the performance of IEEE 802.11p based communication system. The proposed MAC scheme supports high throughput by combining carrier sensing multiple access/collision avoidance (CSMA/CA) with TDMA. The benefits of proposed schemes are verified by simulations. In addition, we discuss some implementation issues including several application scenarios.